2018
DOI: 10.3390/app8050730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fe-Based Shape Memory Alloy (Fe-SMA) as Strengthening Material for Reinforced Concrete Structures

Abstract: This paper aims to evaluate potential of an Fe-based shape memory alloy (Fe-SMA) for strengthening civil structures. Mechanical properties of the Fe-SMA were investigated with a direct tensile test, which showed the stress-induced transformation, stress at fracture of the Fe-SMA, and modulus of elasticity. Heating temperature ranging from 110 • C to 220 • C and pre-straining level ranging from 2% to 8% of the Fe-SMA were considered as variables to provoke a shape memory effect (SME), which generates a recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 32 publications
(54 reference statements)
1
23
0
1
Order By: Relevance
“…Vielfach wird diese Rückstellspannung zur Vorspannung des Betonbauteils eingesetzt. Untersuchungen zur Anwendbarkeit von eisenbasierter Formgedächtnislegierung in Stahlbetonstrukturen (Verbundverhalten, Vorspannwirkung und Auswirkung der Vordehnung auf die verbleibende Steifigkeit und Rückstellspannung) wurden in angestellt.…”
Section: Materialienunclassified
“…Vielfach wird diese Rückstellspannung zur Vorspannung des Betonbauteils eingesetzt. Untersuchungen zur Anwendbarkeit von eisenbasierter Formgedächtnislegierung in Stahlbetonstrukturen (Verbundverhalten, Vorspannwirkung und Auswirkung der Vordehnung auf die verbleibende Steifigkeit und Rückstellspannung) wurden in angestellt.…”
Section: Materialienunclassified
“…Cladera et al [20] and Lee et al [21] studied the applications of Fe-based SMAs. The highly developed SME, high stiffness, high strength, and low production cost of Fe-SMAs have prompted international research on their application in such civil engineering fields as damping, active control, and pre-or post-stressing tensioning of structures [22,23]. Shahverdi et al [6] proposed near-surface mounted (NSM) strengthening techniques that significantly reduce the probability of harm resulting from the corrosion of prestressing members.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that VE-PTMDs performed well in suppressing the vibration of a suspended piping system. With their hysteretic behavior [46], shape memory alloys (SMAs) are another popular energy dissipating material used in control systems [47][48][49][50][51]. As will be further discussed in the following sections, SMAs have unique material properties originating from their transition from martensite to austenite states.…”
Section: Introductionmentioning
confidence: 99%